A strong contender for mental health screening in Latinx immigrant youth: Psychometric properties of the Strengths and Difficulties Questionnaire. (October 2022) - Venta, Amanda; Cuervo, Maria; Bautista, Ashley; Walker, Jesse
Highlights: Rapid increase in asylum-seeking Latinx youth as well as mental health disparity Absence of psychometrically-vetted instruments in Spanish-speaking immigrant youth Propose Strengths and Difficulties Questionnaire to screen Latinx immigrant youth Support for the Total Score, particularly for externalizing behavior problems Support for subscales limited, inadequate internal consistency and reliability Abstract: Latinx youth seeking asylum in the U.S. experience mental health disparity due to exposure to trauma and adversity. Health systems and schools in the U.S. are unprepared to screen for psychopathology in this population, much of which is mono-lingual Spanish-speaking, due to the absence of psychometrically-vetted instruments. The Strengths and Difficulties Questionnaire (SDQ) has strong empirical support as a mental health screener in other demographics. However, there has been no psychometric research in Spanish-speaking immigrant youth and, therefore, the utility in this population remains unknown. The aims of the current study were to examine the SDQ's (a) internal structure, (b) factor structure, (c) test-retest reliability, and (d) concurrent validity. Results are based on N = 110 recently immigrated high school students (60% male, Mage = 19) who completed the SDQ in Spanish. Findings provided support for the Total Score, which displayed evidence of internal consistency, test-retest reliability, and concurrent validity with the Child Behavior Checklist. However, support for the use of the SDQ's subscale scores was limited. In sum, the SDQ Total Score holds promise as a screening instrument for recently immigrated Latinx youth in clinical, health, and educational settings, and use of the subscales requires future research and refinement.